Nasal breathing is superior to oral breathing when performing and undergoing transnasal endoscopy: a randomized trial - Takahashi, Keitaro; Murakami, Yuki; Sasaki, Takahiro; Ueno, Nobuhiro; Tachibana, Shion; Ikeda, Junpei; Ishigaki, Kenichi; Horiuchi, Masashi; Yoshida, Moe; Uehara, Kyoko; Kobayashi, Yu; Sugiyama, Yuya; Kunogi, Takehito; Muto, Mizue; Ando, Katsuyoshi; Muto, Momotaro; Kashima, Shin; Moriichi, Kentaro; Tanabe, Hiroki; Yanagawa, Nobuyuki; Harada, Kazumichi; Teramoto, Takashi; Okumura, Toshikatsu; Fujiya, Mikihiro (Endoscopy, 2022)
Background Transnasal endoscopy presents a technical difficulty when inserting the flexible endoscope. It is unclear whether a particular breathing method is useful for transnasal endoscopy. Therefore, we conducted a prospective randomized controlled trial to compare endoscopic operability and patient tolerance between patients assigned to nasal breathing or oral breathing groups.Methods 198 eligible patients were randomly assigned to undergo transnasal endoscopy with nasal breathing or with oral breathing. Endoscopists and patients answered questionnaires on the endoscopic operability and patient tolerance using a 100-mm visual analog scale ranging from 0 (non-existent) to 100 (most difficult/unbearable). The visibility of the upper-middle pharynx was recorded.Results Patient characteristics did not differ significantly between the groups. Nasal breathing showed a higher rate of good visibility of the upper-middle pharynx than oral breathing (91.9 % vs. 27.6 %; P < 0.001). Nasal breathing showed lower mean [SD] scores than oral breathing in terms of overall technical difficulty (21.0 [11.4] vs. 35.4 [15.0]; P < 0.001). Regarding patient tolerance, nasal breathing showed lower scores than oral breathing for overall discomfort (22.1 [18.8] vs. 30.5 [20.9]; P = 0.004) and other symptoms, including nasal and throat pain, choking, suffocating, gagging, belching, and bloating (all P < 0.05). The pharyngeal bleeding rate was lower in the nasal breathing group than in the oral breathing group (0 % vs. 9.2 %; P = 0.002).Conclusions Nasal breathing is superior to oral breathing for those performing and undergoing transnasal endoscopy. Nasal breathing led to good visibility of the upper-middle pharynx, improved endoscopic operability, and better patient tolerance, and was safer owing to decreased pharyngeal bleeding.